1995
DOI: 10.1177/036354659502300220
|View full text |Cite
|
Sign up to set email alerts
|

Functional Anatomy of the Flexor Pronator Muscle Group in Relation to the Medial Collateral Ligament of the Elbow

Abstract: To describe the relationship of the pronator teres, flexor carpi radialis, flexor digitorum superficialis, and flexor carpi ulnaris muscles to the medial collateral ligament at 30 degrees, 90 degrees, and 120 degrees of elbow flexion, we dissected 11 cadaveric specimens. The flexor carpi ulnaris muscle is the predominant musculotendinous unit overlying the medial collateral ligament in the majority of cases and is the only one at 120 degrees of elbow flexion. The flexor digitorum superficialis muscle is the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(104 citation statements)
references
References 27 publications
4
98
0
2
Order By: Relevance
“…In an anatomical study, Davidson et al 2) stated that the FCU and FDS were the predomi- nant musculotendinous units because of their position directly over the MUCL in the elbow flexion position. Recently, Otoshi et al 9) described that the upper part of the PT ulnar head was attached directly to the medial epicondyle via a thickened joint capsule just anterior to the AOL in all specimens and suggested that muscle activation of the PT directly increases the strain on the medial joint capsule via the humeral branch of the ulnar head.…”
Section: Discussionmentioning
confidence: 99%
“…In an anatomical study, Davidson et al 2) stated that the FCU and FDS were the predomi- nant musculotendinous units because of their position directly over the MUCL in the elbow flexion position. Recently, Otoshi et al 9) described that the upper part of the PT ulnar head was attached directly to the medial epicondyle via a thickened joint capsule just anterior to the AOL in all specimens and suggested that muscle activation of the PT directly increases the strain on the medial joint capsule via the humeral branch of the ulnar head.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the orientation and origin of the flexor-pronator muscles, it seems inherent that these muscles would provide a dynamic support to valgus stress across the medial elbow [37]. Specifically, the flexor carpi ulnaris and portions of the flexor digitorum superficialis lie directly over the anterior bundle of the medial ulnar collateral ligament [37].…”
Section: Active Stabilizersmentioning
confidence: 99%
“…All patients were treated with immobilization of the elbow in a long arm-cast for 4 weeks, followed by a total arm-strength rehabilitation protocol under supervision of a physiotherapist in which valgus load was avoided for 3 months. The flexor carpi ulnaris, flexor digitorum superficialis and pronator teres were strengthened to provide dynamic stabilization , Davidson et al 1995.…”
Section: Methodsmentioning
confidence: 99%